Gender Beyond Binary: Inheritance Rights of Third Gender in Islamic Law—Sri Lankan Legal Recognition and Reform - Saujan Iqbal; Yusuf Sani Abubakr; Seeni Mohamed Mohamed Nafees (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study addresses the question of how Islamic inheritance law accommodates individuals whose gender identity falls outside the male-female binary. It begins by situating the issue within Ilm al-Farā’iḍ, a discipline traditionally premised on gendered share allocations prescribed in the Qur’ān. The research positions itself in the doctrinal debates of Islamic jurisprudence (fiqh), focusing on the classical treatment of khunthā (intersex) and mukhannath (effeminate male) and the principle of awarding the “lesser share” in cases of indeterminate identity (khunthā mushkil). Methodologically, the article employs doctrinal analysis of fiqh texts alongside comparative legal examination across Muslim-majority jurisdictions, including Iran, Egypt, Syria, Iraq, Kuwait, Oman, and Bangladesh. The comparison reveals diverse approaches ranging from conditional recognition following surgery to the formal acknowledgement of “third gender” status. The Sri Lankan context receives particular attention, where the Muslim Intestate Succession Ordinance (MISO) enforces classical fiqh rules, while Article 16(1) of the Constitution shields personal laws from equality-based challenges, resulting in systemic discrimination. The study argues that the Women Empowerment Act (2024), though bypassing MISO guidelines, does not resolve underlying structural barriers. The findings suggest that both legal reform—especially amendments to MISO—and broader societal transformation are necessary to ensure inheritance justice for third-gender Muslims.